Loading mode effect on brittle fracture resistance of cracked component under large-scale yielding. (January 2022) - Shimizu, Kazuma; Ohata, Mitsuru; Shoji, Hiroto; Tanigawa, Hiroyasu; Kato, Taichiro
Abstract: This study assesses the applicability of the Weibull stress for the assessment of the crack-tip plastic constraint effect as well as the mixed mode I and II loading effect on brittle fracture resistance of a ferritic steel. Brittle fracture toughness under different crack-tip plastic constraint conditions and different loading mode conditions was respectively obtained by conducting 3-point bend (3PB) test for single edge cracked specimens with different crack depth subjected to mode I load, and 4-point shear (4PS) test for a single edge cracked specimen with deep crack depth subjected to mixed mode I and II load. By using the results of 3PB tests, the critical Weibull stresses distribution independent of crack-tip plastic constraint was identified, and the critical Weibull stresses obtained by 4PS tests provided significantly smaller distribution than that for 3PB specimen. The mixed mode loading provides the different combined stress field around the crack-tip from that under mode I loading, where the 4PS specimen showed the lower distribution of σ2 /σ1 and σ3 /σ1 than the 3PB specimens. The lower principal stress ratio to be enlarge the fracture driving force was found to have no or much less influence to linear energy release rate for micro-crack, that was employed in the conventional derivation of the Weibull stress. Consequently, the reason why the conventional Weibull stress could not evaluate the effect of loading mode on fracture resistance could be that the linear energy release rate could not exactly take into account the local fracture driving force enlarged due to the combined stress field under mixed mode loading. Highlights: Brittle fracture resistance under different crack-tip plastic constraint conditions and different loading mode conditions. Non-applicability of the conventional Weibull stress to the assessment of loading mode effect on brittle fracture. Local fracture driving force based on non-linear energy release rate for a penny-shaped crack under combined stress field.